2005
DOI: 10.1152/ajprenal.00287.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lithium treatment inhibits renal GSK-3 activity and promotes cyclooxygenase 2-dependent polyuria

Abstract: .-The use of LiCl in clinical psychiatry is routinely complicated by overt nephrogenic diabetes insipidus (NDI), the mechanism of which is incompletely understood. In vitro studies indicate that lithium can induce renal medullary interstitial cell cyclooxygenase 2 (COX2) protein expression via inhibition of glycogen synthase kinase-3␤ (GSK-3␤). Both COX1 and COX2 are expressed in the kidney. Renal prostaglandins have been suggested to play an important role in lithium-induced polyuria. The present studies exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 34 publications
13
112
1
7
Order By: Relevance
“…GSK3, which is inhibited noncompetitively by lithium (16,17), has been studied extensively for its role in cell proliferation and epithelial-mesenchymal transition (13). In our study, lithium treatment resulted in a marked increase in phosphorylated (inactive) GSK3␤, in line with previous studies (18). Because GSK3␤ is a target for phosphorylation by Akt, the increased p-Akt observed with lithium treatment is the potential upstream regulator of this signaling cascade (see above).…”
Section: Regulation Of Pkb/akt By Lithium and Its Role In Cell Survivalsupporting
confidence: 89%
See 1 more Smart Citation
“…GSK3, which is inhibited noncompetitively by lithium (16,17), has been studied extensively for its role in cell proliferation and epithelial-mesenchymal transition (13). In our study, lithium treatment resulted in a marked increase in phosphorylated (inactive) GSK3␤, in line with previous studies (18). Because GSK3␤ is a target for phosphorylation by Akt, the increased p-Akt observed with lithium treatment is the potential upstream regulator of this signaling cascade (see above).…”
Section: Regulation Of Pkb/akt By Lithium and Its Role In Cell Survivalsupporting
confidence: 89%
“…However, it has been shown that inhibition of GSK3␤ by lithium results in enhanced renal COX2 expression in interstitial cells, leading to an increase in local PGE(2) excretion (18), that in turn may counteract AVP actions by causing endocytic retrieval of AQP2 from the collecting duct plasma membrane, thus impairing urinary concentrating ability (20). GSK3␤ knockout mice die from liver degeneration (21); thus, the consequence of GSK3␤ gene deletion on kidney function has yet to be examined.…”
Section: Regulation Of Pkb/akt By Lithium and Its Role In Cell Survivalmentioning
confidence: 99%
“…A feedback mechanism limits insulininduced sodium retention when extracellular fluid volume is expanded [40], which is impaired in rats with hypertension associated with insulin resistance [41]. Inhibition of GSK3 by lithium has been shown to cause urinary concentrating defects [42] and also could inhibit sodium reabsorption in the collecting duct. Renal sodium handling is critical for the maintenance of extracellular fluid volume and BP and its impairment has been associated with the development of hypertension [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…51,52 How the inhibition of GSK3 by lithium ultimately leads to NDI has not been identified but may involve b-catenin, which is increased in expression in lithiuminduced NDI and targeted for degradation by GSK3. 48,[53][54][55] Although basal b-catenin activity is necessary for AQP2 expression in collecting duct cell cultures, overactivation of the canonical Wnt-b-catenin pathway might contribute to lithiuminduced NDI, because it induces transcription of proliferative genes, which is also observed in principal cells of lithium-treated rodents. 56,57 Loss of polarization, which occurs with proliferation, reduces AQP2 expression in vitro.…”
Section: Toxic Effects Of Lithium Treatmentmentioning
confidence: 99%